(untitled) (Research, Society and Development, 2020)
This study aimed to compare the functionality of elderly people who practice physical activity in public environments due to sociodemographic factors and the level of physical activity. Cross-sectional study, carried out with 70 elderly people, of both sexes, who practice physical activity in the Senior Citizens’ Academies (ATI), in the city of Maringá-PR. A sociodemographic questionnaire, the International Physical Activity Questionnaire - (IPAQ) and WHODAS 2.0 were used. Elderly with a partner showed better functionality in relation to mobility (p <0.05). Elderly people with higher education had better functionality in all domains (p <0.05). Elderly black people had worse functionality (p <0.05). Physically active older adults showed better functionality in activities of daily living (p <0.05). It was concluded that the sociodemographic factors and the level of physical activity seem to be intervening factors in the functionality of the elderly who practice physical activities in public environments.